2009
DOI: 10.1098/rspb.2009.0450
|View full text |Cite
|
Sign up to set email alerts
|

Food-supplementing parents reduces their sons' song repertoire size

Abstract: Food-supplemented parents typically produce more offspring, as numerous experiments on vertebrate populations have shown. 'Propagule' (egg or neonate) size and parental care may also be affected, with implications concerning the adult quality of offspring, although few experiments have addressed whether food-supplementing one generation affects adult quality in the next. We conducted a food supplementation experiment on song sparrows (Melospiza melodia) and tested whether song repertoire size, a demonstrated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…B 282: 20150762 rare [4,38]. Zanette et al [4] conducted a food supplementation experiment on song sparrows Melospiza melodia and tested whether male quality (using song repertoire size as a proxy of quality) differed between the adult sons of foodsupplemented and control parents. Surprisingly, Fed parents produced sons with smaller adult song repertoires, who may thus be expected to contribute fewer offspring to the next generation.…”
Section: (C) Reproductive Successmentioning
confidence: 99%
“…B 282: 20150762 rare [4,38]. Zanette et al [4] conducted a food supplementation experiment on song sparrows Melospiza melodia and tested whether male quality (using song repertoire size as a proxy of quality) differed between the adult sons of foodsupplemented and control parents. Surprisingly, Fed parents produced sons with smaller adult song repertoires, who may thus be expected to contribute fewer offspring to the next generation.…”
Section: (C) Reproductive Successmentioning
confidence: 99%
“…2008). Many studies across avian species have shown that larger nestlings receive the lion ' s share of parental provisioning at the cost of their smaller nestmates (Price and Ydenberg 1995, Oddie 2000, Forbes et al 2002, Zanette et al 2009). Where host nestlings are smaller than the cowbird, female host nestlings may be expected to be the most disadvantaged (Fig.…”
Section: (D)mentioning
confidence: 99%
“…Infection affected the condition-dependent nature of these calls, which are used in an anti-predator context ). Zanette et al (2009) found that young Song Sparrows Melospiza melodia fed by foodsupplemented parents sang less diverse songs than young from unfed parents, and discussed the possible negative effects of food-supplementing wild populations for conservation purposes. Supplemented parents laid larger clutches and lighter eggs, thus their young had to accelerate their growth more than control birds, at the detriment of their learning abilities and song output once they become adults.…”
Section: Acoustic Signals and Introduced Diseasesmentioning
confidence: 99%